2014
DOI: 10.1145/2601097.2601213
|View full text |Cite
|
Sign up to set email alerts
|

Form-finding with polyhedral meshes made simple

Abstract: We solve the form-finding problem for polyhedral meshes in a way which combines form, function and fabrication; taking care of userspecified constraints like boundary interpolation, planarity of faces, statics, panel size and shape, enclosed volume, and last, but not least, cost. Our main application is the interactive modeling of meshes for architectural and industrial design. Our approach can be described as guided exploration of the constraint space whose algebraic structure is simplified by introducing aux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 29 publications
1
75
0
2
Order By: Relevance
“…Vouga et al [2012] show how to rationalize any selfsupporting shape by a self-supporting planar quad mesh, but do not directly design it. Form-finding with polyhedral meshes in static equilibrium is the topic of [Tang et al 2014], of which our paper is a follow-up.…”
Section: Prior Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Vouga et al [2012] show how to rationalize any selfsupporting shape by a self-supporting planar quad mesh, but do not directly design it. Form-finding with polyhedral meshes in static equilibrium is the topic of [Tang et al 2014], of which our paper is a follow-up.…”
Section: Prior Workmentioning
confidence: 99%
“…In this way, the planarity constraint is quadratic. This approach motivated the systematic avoidance of constraints of degree ≥ 3 by Tang et al [2014] which forms the basis of the present paper. Extensive comparative tests showed that it clearly outperforms previous work in terms of the combination of speed and high accuracy of constraint satisfaction.…”
Section: Prior Workmentioning
confidence: 99%
See 3 more Smart Citations